Chicken soup for the soul grieving and recovery : 101 inspirational and comforting stories about surviving the loss of a loved one - Canfield, Jack 1944-; Hansen, Mark Victor; Newmark, Amy (Cos Cob, Connecticut Chicken Soup for the Soul Publishing, 2011)
A collection of 101 true personal stories from regular people about losing loved ones, covering all the phases of mourning and recovery, with emphasis on how to accept the loss and move forward.
Keywords: Death -- Literary collections; Bereavement -- Literary collections; Death -- Anecdotes; Bereavement -- Anecdotes; Loss (Psychology)